Litigation Financing – A Conceptual Framework - Ngwakwe, Collins (Acta Universitatis Danubius. Juridica, 2022)
Financial costs, which accompany the pursuit of legal redress is documented in the literature as one of the impediments, which deter litigants from seeking their legal rights, redress, or remedies. However, this domain of discussion, which pervades finance and law, is not very common in research literature. Objective: Accordingly, this paper aims to provide a conceptual understanding on the concept of litigation financing and a framework therefrom. Prior work: the paper relies on prior literature theorisations of litigation financing. Approach: The approach is conceptual with reliance on critical review of extant authoritative research discussions and culminates in a brief conceptual framework for further research on litigation finance. Findings: litigation financing is emerging in the investment arena and in legal practice. It holds potential for rewarding financial returns to investors (funders) if the risks are minimized. Implication: it offers practical, theoretical, and academic implications for legal policy makers, attorney firms, litigation investors (funders), and scholars of finance and law in business schools and law faculties. Value: it conceptualises litigation financing by adopting an interdisciplinary stance – crisscrossing the law and finance and development a novel conceptual framework of litigation financing for further research.